Extensive Reading Programme as a Strategy to Improve English Language Proficiency among Young Adult Learners: Initial Perceptions - Mei Lick Cheok (English Language Teaching and Research Journal (ELTAR-J), 2020)
With the amount of empirical evidence available to prove the benefits of Extensive Reading (ER) for the development of language proficiency and literacy, those outside the teaching fraternity would think that language teachers and schools would be scrambling to embrace and adopt ER. This is not what I have experienced in a number of primary and secondary schools, including the institution that I am currently teaching. From my own experience as an avid reader and the research papers I have read, I am convinced of the magic of ER. This paper described the process and challenges in planning and developing ER through a 15-minute Silent Reading Programme (15-min SRP) that was carried out in a class of 18 pre-university students and preliminary findings on students’ perceptions towards the implementation of the programme. The paper concluded with recommendations that can help other ER start-ups especially schools in Malaysia.